2007
DOI: 10.1007/s00068-007-6053-5
|View full text |Cite
|
Sign up to set email alerts
|

An in Vivo Experimental Comparison of Stainless Steel and Titanium Schanz Screws for External Fixation

Abstract: There is no clinically relevant substantial advantage in using either SS or Ti pins on reducing pin loosening or pin track irritation/infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…On day 14, visible clinical findings at each pin site were classified according to pin site infection criteria as no infection, inflammation or serous drainage without frank purulence, or frank purulence. 26,27 Clinical determination of infection was defined as all three observers being in agreement. After evaluation by eye, the animals were sacrificed and the bone and soft tissue around the pin were retrieved.…”
Section: Evaluation Of Bactericidal Effectmentioning
confidence: 99%
“…On day 14, visible clinical findings at each pin site were classified according to pin site infection criteria as no infection, inflammation or serous drainage without frank purulence, or frank purulence. 26,27 Clinical determination of infection was defined as all three observers being in agreement. After evaluation by eye, the animals were sacrificed and the bone and soft tissue around the pin were retrieved.…”
Section: Evaluation Of Bactericidal Effectmentioning
confidence: 99%
“…This difference may be due, in part, to the cyclic loading by the animal which may delay or partly inhibit the formation and maintenance of bony on-growth. 5 This study was designed to evaluate the removal of intramedullary nail interlocking screws following a nonunion in a canine model. Based on Ganser et al, 5 it was hypothesized that explantation torques would be greater than the intraoperative insertional torque for the screws adjacent to the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…5 This study was designed to evaluate the removal of intramedullary nail interlocking screws following a nonunion in a canine model. Based on Ganser et al, 5 it was hypothesized that explantation torques would be greater than the intraoperative insertional torque for the screws adjacent to the fracture. The limbs were analyzed in two groups: unloaded and loaded to failure in torsion prior to screw removal.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] , and titanium is now used as a dental implant material 7) . Ganser et al 8) reported the clinical benefits of stainless steel and titanium for reducing pin track irritation/infection and pin loosening during external fracture fixation of the hind limbs of sheep, and found no clinically relevant substantial advantage in using either stainless steel or titanium pins. Choi et al 9) performed a clinical comparative study between titanium and stainless steel for microsurgical cerebral aneurysm clip implants.…”
Section: Introductionmentioning
confidence: 99%